Contemporary research on renal cell carcinoma: basic and clinical developments - Staehler, Gerd 1939-2014; Pomer, Sigmund (Springer Berlin Heidelberg, 1994)
This book describes the scientific and clinical developments in the treatment of renal cell carcinoma (RCC). Its purpose is to elucidate the field of immunotherapy, immunobiology and to report recent data on basic and clinical research, including several of the most discussed trends. Of particular interest are the current achievements of photodynamic therapy and the results of metastasis surgery, especially for bone, lung, and liver disease. The interdisciplinary cooperation between surgeons, urologists, immunologists and biologists has led to promising new modalities that have already resulted in improved survival of patients. Those interested in clinical topics will benefit from this book by receiving a review of the clinical aspects of RCC
Keywords: Aufsatzsammlung; Hypernephrom